2006
DOI: 10.1111/j.1551-2916.2006.00976.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Microwave Effect During Hybrid Sintering

Abstract: A microwave/conventional hybrid furnace has been used to sinter three ceramics with different microwave absorption characteristics under pure conventional and a range of microwave/conventional hybrid heating regimes. The precursor powder particle size was also varied for each material. In each case it was ensured that every sample within a series had an identical thermal history in terms of its temperature/time profile. An increase in both the onset of densification and the final density achieved was observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
100
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(111 citation statements)
references
References 19 publications
11
100
0
Order By: Relevance
“…Microwave radiation for sintering of ceramic components has recently appeared as a newly focused scientific approach [9][10][11][12][13][14][15][16]. Microwave sintering has several advantages such as rapid end volumetric heating, improved production rate, enhancement in densification and grain growth prohibition of ceramics [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Microwave radiation for sintering of ceramic components has recently appeared as a newly focused scientific approach [9][10][11][12][13][14][15][16]. Microwave sintering has several advantages such as rapid end volumetric heating, improved production rate, enhancement in densification and grain growth prohibition of ceramics [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…However, kaolinite, mullite and alumina present low dielectric losses, and it is known that the development of liquid phase increases the body's dielectric loss, thus considerably increasing the microwave absorption characteristics of compacts. Other authors 27,28 have shown that materials with very low dielectric loss display an extremely small, almost negligible difference in densification when processed by microwave energy compared to conventional heating.…”
Section: Resultsmentioning
confidence: 99%
“…Although recent results from Loughborough have now confirmed the existence of the socalled 'microwave effect' during ceramic sintering [9], it is believed that the major effect influencing these results is that a much faster heating rate was used. Due to the volumetric nature of the hybrid heating, 20 o C min -1 could be used without risking any damage to the samples from thermal stresses, whilst the radiant heating was limited to only 7 o C min -1 .…”
Section: Resultsmentioning
confidence: 99%